2014
DOI: 10.1007/s10266-014-0180-3
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive strength of self-adhesive resins to lithium disilicate ceramic and dentin: effect of dentin chelating agents

Abstract: The aim of this study was to test the effect of different chelating agents on microtensile bond strength (MTBS) of self-adhesive resin cements to dentin. The occlusal surfaces of extracted human mandibular molars (N = 80) were cut horizontally to expose sound dentin. The teeth were randomly divided into four groups (n = 20 per group) and dentin surfaces were conditioned according to one of the following methods: group C: no treatment (control group); group CH: 0.2 % chitosan; group E: 17 % ethylene diamine tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
1
4
0
4
Order By: Relevance
“…This result can be attributed to the low pH of EDTA, which acts as a calcium chelator, resulting in removal of the thick endodontic smear‐layer and slight demineralization of the dentin surface . This result was supported by other studies , which revealed that previous treatment with EDTA increased the bond strength of self‐etching adhesive systems or self‐adhesive luting cements . As a mild chelating agent, EDTA could dissolve the hydroxyapatite and non‐collagenous protein selectively, avoiding major alterations of the native collagen fibrillar structure .…”
Section: Discussionmentioning
confidence: 59%
“…This result can be attributed to the low pH of EDTA, which acts as a calcium chelator, resulting in removal of the thick endodontic smear‐layer and slight demineralization of the dentin surface . This result was supported by other studies , which revealed that previous treatment with EDTA increased the bond strength of self‐etching adhesive systems or self‐adhesive luting cements . As a mild chelating agent, EDTA could dissolve the hydroxyapatite and non‐collagenous protein selectively, avoiding major alterations of the native collagen fibrillar structure .…”
Section: Discussionmentioning
confidence: 59%
“…Recently, the instigation of a simplified acid ceramic primer has claimed to perform a mild acid silanization and etching using a single solution. 9 This monobond Etch & Prime (MEP) and one bottle system combine silane and ammonium polyfluoride on the basis of trimethoxy propyl methacrylate to show a thin chemically bonded layer. 10 The introduction of this primer was to simplify the bonding procedure by priming glass and etching ceramics using a one-step process.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…It is well known that restorative ceramic materials require a clinical stage of bonding to tooth structures with adhesive resin cements (2). Thus, the optical behavior of a ceramic restoration is determined by the combination of the color of the underlying tooth structure, the thickness/composition of the ceramic veneer, and the color of the luting cement (3).…”
Section: Introductionmentioning
confidence: 99%